Sistem Pendukung Keputusan dengan Metode Electre II Dalam Menentukan Aplikasi Belanja Online Terbaik - Nur Hasanah Lubis; Irfan Sudahri Damanik; Widodo Saputra (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
With the development of the times, online shopping applications have begun to emerge that make it easier for buyers and sellers to sell and buy goods without the hassle of running. But with so many applications that make people confused about which application is best used. Therefore the author wants to help the community in determining the best application by using a decision support system using the Electre II method, it is hoped that this research can help recommend the best online applications for the community.